(untitled) (Revista Brasileira Multidisciplinar, 2026)
Large cities benefit from epidemiological research and vector infestation studies to plan actions against dengue. However, in smaller areas, the lack of comprehensive studies results in complications when cases increase, affecting both managers and the population. This work aims to understand the relationship between rainfall, confirmed dengue cases, and infested properties in Abaiara-CE from 2014 to 2017. The methods included documentary, quantitative, and qualitative research, with data collected through the Rapid Index Survey (LIRAa) and the Laboratory Environment Manager (GAL). Rainfall data were obtained from FUNCEME. Correlation tests between rainfall indices and Aedes aegypti infestation were conducted using the R program, and graphs were generated in Excel. A positive correlation (0.60) was observed between the Property Infestation Index and the accumulated rainfall in each inspection cycle. A positive correlation (0.55) was also found between confirmed dengue cases and rainfall. This correlation was stronger in 2014, 2015, and 2017. A weak negative correlation (-0.26) was noted between the duration of the previous cycle and the number of positive properties in the following cycle. The results are similar to those found in large cities. Data from endemic agents are essential, and their analysis can support actions to combat arboviruses transmitted by A. aegypti, even in small cities.